Model e-dokumentiranja patronažne zdravstvene nege - Rajkovič, Uroš (Obzornik zdravstvene nege, 2006)
This article presents a system approach used in the development of electronic documentation for community nursing. Documentation is viewed as an information model for organizing and managing processes. Community nurse plans the nursing process upon gathering and evaluating of information regarding patient''s health and his/her family status. Documentation is in this way considered as a basis for successful work of the health team and as a way of ensuring quality in nursing care. The article describes a prototype model of software solution for e-documenting in community nursing.
Keywords: dokumentacija; modeliranje; Nursing Care; patronažna služba; Zdravstvena nega